Factors influencing leisure participation among female academicians in a Malaysian Public University - Yarima, Mahmud Zubaina (2016)
Introduction: Leisure participation is beneficial towards maintaining a healthy living. It can be gained not only from vigorous activities but also through performing passive activities. Objective: The main objective of the study is to determine the factors influencing leisure participation among female academicians in Universiti Putra Malaysia (UPM), Serdang. Methodology: A cross- sectional study was conducted among female academicians in UPM from December 2014 to March 2015, involving 654 respondents, selected using simple random sampling method. A self-administered questionnaire followed by e-mail was used as method of data collection. The questionnaire was validated and consisted of seven sections namely socio-demography factors, perceived social support from family members and friends and also perceived time constraints at home and work place. The measurement scales used were a 5-point likert (0 to 4) for accessibility to leisure related facilities at home and work place and nominal scales (Yes vs No) for health status and leisure participation questionnaire were measured using a 5-point likert scale (0 to 4). The analysis involved descriptive, bivariate (Independent T-test and correlation) and multivariate analyses (linear regression). The level of significance was set at 0.05 Results: The mean scores for physical activity were 4.17± 4.26 and non- physical activity was 28.93±8.88. The mean age of the respondents was 42.21± 8.55 years old. Most of the respondents were Malay (70.0%), Muslims (70.1%), married (67.1%), senior lecturers (42.4%), Malaysians citizen (95.6%), high perceived social support received from family members (68.8%) and friends (66.8%), high perceived time constraints at home (72%) and workplace (50.9%), had high access to leisure-related facilities either at home (60.0%) or workplace (85.2%) and did not have chronic illness (58.7%). The total mean score for leisure participation in physical activities was 4.17± 4.26 and 28.93±8.88 for non- physical activities. The top five activities with the highest mean score for physical activities were regular exercise (1.43 ±1.27), evening walk (0.90 ±1.25), jogging (0.48±0.96), playing golf (0.14 ±0.50) and swimming (0.31±0.71). Meanwhile, the top five non-physical activities with the highest mean scores were browsing (2.96 ± 1.19), watching television (2.82±1.25), listening to the radio (2.64± 1.42), reading (2.63± 1.26) and cooking (1.97± 1.54) However, the final model showed only age (B=-0.107, 95% CI: -0.164, - 0.051, p=0.001), accessibility leisure-related facility at home (B=1.030, 95% CI:-1.669, 0.392 P=0.002) and health status (B=1.550, 95% CI: - 2.184,-0.916, p=0.001) were the only significant predictors of leisure participation in physical activity. Whereas, age (B=-0.211, 95% CI:-0.342,-0.213, P=0.001) was the only significant predictor for leisure participation in non-physical activity. Unfortunately, both models revealed remarkably low Nigerkerk R2 values of 15.8% and 2.8% respectively. Conclusion: The results of this study indicate a considerably low level of leisure participation in physical activity as evidenced by the low mean score for each of the physical activities listed and also the total mean score as compared to non-physical activity. Age, health status and accessibility to leisure facilities at home were significantly predicting the participation of the respondents into physical activity during leisure, whereas non- physical activity was only significantly predicted by age. Relevant authorities should be acknowledged on the importance of providing leisure facilities in the residential area or in the neighbourhood such as gymnasium to enable them to participate in leisure activities.